Understanding Peptide Binding in Class A G Protein-Coupled Receptors - Tikhonova, Irina G. (Mol Pharmacol, 2019)
Many physiologic processes are controlled through the activation of G protein-coupled receptors (GPCRs) by regulatory peptides, making peptide GPCRs particularly useful targets for major human diseases such as diabetes and cancer. Peptide GPCRs are also being evaluated as next-generation targets for the development of novel antiparasite agents and insecticides in veterinary medicine and agriculture. Resolution of crystal structures for several peptide GPCRs has advanced our understanding of peptide-receptor interactions and fueled interest in correlating peptide heterogeneity with receptor-binding properties. In this review, the knowledge of recently crystalized peptide-GPCR complexes, previously accumulated peptide structure-activity relationship studies, receptor mutagenesis, and sequence alignment are integrated to better understand peptide binding to the transmembrane cavity of class A GPCRs. Using SAR data, we show that peptide class A GPCRs can be divided into groups with distinct hydrophilic residues. These characteristic residues help explain the preference of a receptor to bind the C-terminal free carboxyl group, the C-terminal amidated group, or the N-terminal ammonium group of peptides.